APLIKASI LIMBAH CAIR BIOGAS SEBAGAI PUPUK ORGANIK PADA TANAMAN JAGUNG MANIS (Zea mays var. saccharata Sturt.) - Emy Hidayati; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sweet corn (Zea mays var. Saccharata Sturt) is one of the crops which liked by people because it has a good taste, and sweeter than ordinary corn. One of the effort that can be do to improve and increase soil fertility is apply bioslurry organic fertilizer. Bioslurry is the end product of the animal waste processing for biogas energy.  Bioslurry containing elements that need for sweet corn such as N, P, K. This study aimed to know the effect of bioslurry and get the best dose of bioslurry on the growth and production of sweet corn. This research was experimently using a randomized block design (RBD), which consists of 6 treatments and 4 replications. Parameters measured were plant height (cm), number of leaves (pieces), flowers appear male and female flowers (HST), weight cob with husk and without husk (gram), cob diameter (cm) and production per plot (gram). The results showed that the bioslurry fertilizer application significantly affected plant height, number of leaves, flowers appear male and female flowers, weight cob with husk and cob without husk, cob diameter, and production per plot. Application at dose  of  7.5 liters / 4.5 m² give the best results on the growth and production of sweet corn than other treatments.   Keywords: sweet corn, bioslurry fertilizer